The effects of bursty bulk flows on global‐scale current systems. Issue 6 (13th June 2017) - Yu, Yiqun; Cao, Jinbin; Fu, Huishan; Lu, Haoyu; Yao, Zhonghua
Abstract: Using a global magnetospheric MHD model coupled with a kinetic ring current model, we investigate the effects of magnetotail dynamics, particularly the earthward bursty bulk flows (BBFs) produced by the tail reconnection, on the global‐scale current systems. The simulation results indicate that after BBFs brake around X = −10 R E due to the dipolar "magnetic wall, " vortices are generated on the edge of the braking region and inside the inner magnetosphere. Each pair of vortex in the inner magnetosphere disturbs the westward ring current to arc radially inward as well as toward high latitudes. The resultant pressure gradient on the azimuthal direction induces region‐1 sense field‐aligned component from the ring current, which eventually is diverted into the ionosphere at high latitudes, giving rise to a pair of field‐aligned current (FAC) eddies in the ionosphere. On the edge of the flow braking region where vortices also emerge, a pair of region‐1 sense FACs arises, diverted from the cross‐tail duskward current, generating a substorm current wedge. This is again attributed to the increase of thermal pressure ahead of the bursty flows turning azimuthally. It is further found that when multiple BBFs, despite their localization, continually and rapidly impinge on the "wall, " carrying sufficient tail plasma sheet population toward the Earth, they can lead to the formation of a new ring current. These results indicate the important role that BBFs play in bridging the tail and the inner magnetosphere ring current and bring new insight into the storm‐substorm relation. Key Points: BBFs generate vortices not only on the edge of flow braking region but also inside inner magnetosphere, disturbing the westward ring current FACs diverted from the ring current at high latitude, caused by local pressure gradient Global MHD model coupled with a kinetic ring current model allows for exploring mesoscale structure in the coupled tail‐inner region